More ulam for your brain: a review on the potential role of ulam in protecting against cognitive decline - You, Yeexing; Suzana Shahar,; Hasnah Haron,; Hanis Mastura Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ulam is the South East Asian traditional vegetables which contains high total phenolic content and exhibits antioxidant activity. Several studies have reported the potential of neuroprotective effect of ulam. The objective of this review article was to highlight the total phenolic content (TPC) and antioxidant activity of ulam and the roles of phenolic content that can contribute to attenuation of cognitive decline. The review includes randomized controlled trial and experimental studies from year 2007 to 2017. In this review, PRISMA method was used to report the results (n=15). Phenolic compounds, ie plants’ second metabolites of selected ulam in South East Asia were also discussed in this review, with respect to its potential for health promotion which and reducing the risk of cognitive disease. Oenanthe javanica (selom), Ocimum basilicum (daun selasih) and Anacardium occidentale L. (pucuk gajus) were ranked in the top three highest TPC among all the selected ulam. In general, Polygonum minus (kesum), Anacardium occidentale L. (pucuk gajus) and Cosmos caudatus (ulam raja) exhibited high DPPH radical scavenging activity whereas Anacardium occidentale L. (pucuk gajus) exhibited highest ferric ion reducing potential (FRAP) among all the selected ulam in South East Asia countries. Overall, some studies had shown Centella asiatica (pegaga), Oenanthe javanica (selom), Polygonum minus (kesum), Ocimum basilicum (daun selasih) and Murraya koenigii (daun kari) are beneficial in improving cognitive status and mood. The bioactive compounds in ulam may exhibit neuroprotective effects but human studies are still lacking in exploring the relationship between ulam consumption and cognitive status.